The Role of Mutual Trust and Mutual Recognition in the Functioning of the European Public Prosecutor’s Office - Valéria Ružičková (Časopis pro Právní Vědu a Praxi, 2022)
This article aims to examine the situations in the European Public Prosecutor’s Office proceedings, in which the use of mutual trust and, consequently, mutual recognition is possible and deliberate on whether the role of these principles is significant or rather minor. By doing so, it sheds light on the nature of the principle of mutual trust and mutual recognition as well as the mutual recognition mechanisms which are applicable in criminal proceedings in general. It explains, with regard to the European Public Prosecutor’s Office, the possibility of their use in the European Public Prosecutor’s Office proceedings taking into account the limitations of the principle of mutual trust and mutual recognition.